Amicus Plato, sed magis amica veritas. The care of souls of mixed marriages - KRAJCZYŃSKI, JAN (Prawo Kanoniczne, 2019)
The author presents arguments of legal nature relating to the ministry of marriages contracted by two baptised persons out of whom only one person belongs to the Catholic Church and is committed to abide by the 1125.1 provision of the canon law. Having specified human and religious factors that define this ministry, the author defines rules to be accepted in particular law in terms of the ministry of mixed marriages.